Language-related acculturative hassles and their association with mental health of minors with refugee background living in Germany - Braig, Johanna; Schmees, Pia; Kilinc, Yasemin; EL-Awad, Usama; Nilles, Hannah; Kerkhoff, Denny; Rueth, Jana-Elisa; Lohaus, Arnold; Eschenbeck, Heike (Frontiers in Psychology, 2025)
IntroductionThe public debate on migration often focuses on refugees’ cultural adaptation, with language barriers being a key concern. Previous research demonstrated associations of mental health with acculturative hassles but there is little longitudinal research. Therefore, this study examines the longitudinal relationship between the mental health of refugee minors and language-related acculturative hassles concerning the host country’s language. We assume that internalizing symptoms are associated with language hassles and predict them over time, for externalizing symptoms no assumptions were made.MethodsA non-clinical sample of 11–19-year-old minors with refugee background living accompanied in Germany (n = 63) answered self-report questionnaires on mental health, language proficiency, and language related hassles twice at intervals of approximately 1 year.ResultsBaseline language hassles and internalizing symptoms (ΔR2 = 0.06) but not externalizing symptoms predicted follow-up language hassles.DiscussionOur study shows initial, longitudinal indications that impaired mental health may be a risk factor for language hassles. This is considered important for affected minors and their caregivers, e.g., for education and peer contact. Replication of the findings with a larger sample size is recommended.